Strengthening Social Concern Through The “Recehmu Bermanfaat” Program: A Digital Based Micro Fundraising Innovation - Maha Sari, Ardystia; Astriawati, Ningrum; Barokah; Ratna Sari, Dwiani; Nuriil Tardesi, Risnaliyah; Zuhroh, Ulfa (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2025)
The Recehmu Bermanfaat program is a community service initiative aimed at building social awareness and solidarity through digital-based micro-fundraising. This program was initiated to address the lack of an organized platform for people wishing to distribute small donations in a practical and transparent manner. The method used in this community service program is Participatory Action Research (PAR). Implementation steps include initial observation to identify potential participants, program planning with residents, digital donation collection through bank transfers and the use of WhatsApp groups/status, information dissemination through social media such as Instagram, and periodic evaluations to ensure sustainability and accountability. The implementation results show high community enthusiasm with an increase in the number of donations and active participation in aid distribution activities, such as the distribution of rice packages in the Jumat Berkah program, assistance to orphans, and purchases of goods from small traders. This digital approach has been proven to facilitate transparent fund management, expand the reach of donations, and revitalize the values ​​of mutual cooperation and social awareness within the community. These findings confirm that micro-fundraising through digital-based small donations can be an effective, sustainable service model, and has the potential to be replicated in other communities with adjustments to local characteristics.